Grow your own vegetables - Klein, Carol, 1945- (Mitchell Beazley ; Distributed in the U.S. and Canada by Octopus Books USA, 2010)
A guide to growing more than forty different crops, including artichokes, garlic, sweet potatoes, and zucchini, with advice of sowing seed, harvesting, storing, cooking, and dealing with pests.